Somatic, Auditory, Visual, Intellectual Learning Model in Improving Vowel Pronunciation for 3rd Class Deaf Students - Agusliati, Eka; Aprilia, Imas Diana (Angstrom Centre of Education, 2022)
The ability to pronounce vowels in deaf students is still low, the indications are the occurrence of replacement, addition, and even the omission of phonemes. On the other hand, there is the unpreparedness of the teacher in setting the right model and method during articulation exercises, ignoring the basic receptive and expressive language skills of deaf students, allegedly as a form of teacher failure in practicing articulation both during individual and classical learning. For this reason, it is necessary to have a learning model that can accommodate the needs of deaf students to articulate correctly. This study aims to determine the effectiveness of the SAVI (Somatic Auditory Visual Intellectual) learning model in improving the pronunciation of vowels in class III deaf students. The approach used in this research is quantitative with the type of experimental research in the form of SSR (Single Subject Research) with ABA design. Data was collected using Observation and Treatment Tests carried out on one deaf child. The results of the study were that in the baseline-1 condition, the intervention increased by a value of 73.33, the intervention in Baseline-2 decreased by a value of 60.83, and although the intervention in Baseline-2 experienced a decrease, the data obtained was much better than the baseline-1, which was 26.66. In conclusion, the Somatic, Auditory, Visual, and Intellectual learning model affects improving the pronunciation of vowels in Deaf Students. For this reason, teachers must pay attention to and develop sensory modalities in deaf students in an integrated and holistic way in learning articulation.